America between the wars : from 11/9 to 9/11 : the misunderstood years between the fall of the Berlin Wall and the start of the War on Terror - Chollet, Derek H. (BBS PublicAffairs, 2008)
When the Berlin Wall collapsed and the Cold War ended on November 9, 1989, the West declared victory: democracy and free markets had prevailed and the United States emerged as the triumphant superpower. The tension that had defined a generation was over, and it seemed that peace was at hand. The next twelve years rolled by in a haze of complacent self-congratulation--what some now call a "holiday from history." When September 11, 2001, set the U.S. on a new path, confused Americans asked: How did we get here? Foreign policy experts Chollet and Goldgeier examine how the decisions and debates of those years shaped the events, arguments, and politics of the world we live in today. This book tells the story of a generation of leaders grappling with a moment of dramatic transformation--changing how we should think about the recent past, and uncovering important lessons for the future.--From publisher description